Impact of Organizational Support And Technology Competence In E-Commerce Adoption On SMEs Performance In Jabodetabek Region - Ratnaningsih Hidayati; Ririh Kusuma Permatasari; Ashry Noviana Fajry (Pusat Pendidikan dan Pelatihan Perdagangan, 2019)
E-commerce has changed the ways of doing business in many business sectors, including Small Medium Enterprises (SMEs) sector. However, SMEs encountered varied challenges in adopting e-commerce to their business. This research analyzed organizational support and technology competence in e-commerce adoption on SMEs performance in Indonesia, specifically in Jabodetabek region. A quantitative approach was applied in this study, with a Likert-scale questionnaire as a tool to determine the impact of internal factor regarding e-commerce adoption on the SMEs performance. An ordinary linear regression analysis was conducted to test the hypothesis. The results showed that the variables of organizational support and technology competence simultaneously affect the performance improvement on e-Commerce adoption by SMEs in Jabodetabek region